Pengaruh Sistem Informasi Akuntansi dan E-Commerce terhadap Kinerja UMKM di Wilayah Banyuwangi - Wulan Nur Indahsari; Moh Halim; Rendy Mirwan Aspirandy (LPPM POLITEKNIK LP3I BANDUNG, 2023)
This study aims to determine the effect of accounting information systems and e-commerce on the performance of MSMEs in the West Banyuwangi Region. The population used in this study is MSMEs located in the Banyuwangi Region and registered with the Banyuwangi City Cooperative and Trade Office. The sample in this study was selected using a purposive sampling technique. MSMEs that were sampled in this study were MSMEs in the West Banyuwangi Region. The number of questionnaires distributed in this study were 78 questionnaires with questionnaire data that could be processed as many as 72 questionnaires. The data analysis technique uses multiple linear regression analysis. In addition, the results of the study show that either simultaneously or partially the variables of accounting information systems and e-commerce have a significant influence on the performance of MSMEs.